Geographical Tatoos - Cazetta, valeria (Geografares, 2014)
The article deals with maps tattooed on bodies. My interest in studying the corporeality is inserted in a broader project entitled Geographies and (in) Bodies. There is several published research on tattoos, but none in particular about tattooed maps. However some of these works interested me because they present important discussions in contemporary about body modification that helped me locate the body modifications most within the culture than on the nature. At this time, I looked at pictures of geographical tattoos available in several sites of the internet.Keywords: tattoo; tattooed maps; space; body.